Arterial Access in Patients With De Novo Acute Coronary Syndrome Undergoing Coronary Angiography. (April 2017) - Abdul Jabbar, Ali; Mufti, Omar; Sabol, Angeline; Markert, Ronald; White, Bryan; Broderick, George
Bleeding is a major limitation of antithrombotic therapy among invasively managed patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACSs). Randomized clinical trials have generally failed to favor either the femoral or the radial arterial approach for coronary angiography or intervention in NSTE-ACS. In 561 hospitalized patients with a new diagnosis of NSTE-ACS referred for coronary angiography, 364 and 197 patients underwent the femoral and the radial approach, respectively. Femoral and radial access did not differ in bleeding complications in the first 72 hours (8 of 364 or 2.2% vs 8 of 197 or 4.1%, P = .21), duration of hospitalization (4.67 ± 5.02 vs 4.51 ± 4.81, P = .28) nor in-hospital mortality (0.8% vs 0.5%, P = .67). Contrast volume was higher for femoral versus radial cases (204 ± 119 vs 168 ± 104, P < .001). In patients with de novo NSTE-ACS without prior cardiac bypass, radial and femoral arterial access did not differ in instances of bleeding within the first 72 hours postoperatively, length of hospital stay, or in-hospital mortality. Less contrast was used in radial cases, which may represent an advantage for patients with renal insufficiency.